Construction of S-box based on chaotic Boolean functions and its application in image encryption. Issue 3 (April 2016) - Khan, Majid; Shah, Tariq; Batool, Syeda
Abstract In numerous encryption frameworks, the first information is changed into encoded form by applying nonlinear substitutions and affecting diffusion. The goal of the nonlinear change is to accomplish high level of randomness in the image content. The choice of the source of randomness is critical because the success in cryptanalysis is demarked by the characteristics identified in the encrypted data. The chaotic frameworks show random conduct that is suitable for encryption applications where nonlinear transformations are needed in the middle of plaintext and the scrambled information. The application of nonlinear functional chaos-based system with embedded chaotic systems and binary chaotic sequences can prompt randomness and diffusion in the information. In addition to the high state of randomness, the requirement for various round keys is needed in a run of the mill substitution–permutation process. The proposed strategy kills the requirement for different round keys, which is suitable for high-speed communication frameworks. The measurable analyses performed on the proposed nonlinear algorithm which show improvement in encryption quality and safety against numerous brute-force and statistical attacks. Also, the proposed framework demonstrates high safety against differential and linear cryptanalysis.